An analytical reading of the mechanisms of selecting an effective teacher for the primary stage according to some personal characteristics - toumi, tayeb (Journal of Social Sciences and Humanities, 2023)
The following research paper touched on the development of a proposed vision for some Personal characteristics during the selection of a successful teacher, as it is common knowledge in the educational right that there are several episodes that must be taken care of because they have an influential weight in the educational dimension that all actors in it need, which makes us here and in this paper To talk briefly about the general characteristics of the teacher’s personal qualities, which are represented in their mental, cognitive and social aspects. In addition to this, the second question, which is the core of our research paper, was answered by presenting the proposed perception about some of the psychological characteristics of choosing a successful teacher; All this was done based on some previous studies that supported the researcher in his literary presentation and during the discussion of his hypotheses. And in the last thing we wanted to ask is our affirmation that these psychological characteristics in the educational field are very important and must be characterized by the teacher in order to be successful and effective in the classroom, as attention has now become the goal of everyone who wants to access education to the best visions, according to what educational specialists appeal to.